Fredholm quasi-linear manifolds and degree of Fredholm quasi-linear mapping between them - Abbasоv, A. (Ukrains’kyi Matematychnyi Zhurnal, 2011)
In this article a new class of Banach manifolds and a new class of mappings between them are presented and also the theory of degree of such mappings is given.